IMPLEMENTASI SISTEM MONITORING KELEMBABAN TANAH, PH TANAH DAN INTENSITAS CAHAYA TANAMAN LAHAN TERBUKA DENGAN WSN BERBASIS MODUL NRF24L01 - Aurellia, Shakira Nuranissa (Universitas Lampung, 2024)
Soil conditions such as moisture, pH, and light intensity at BBPP Lembang are still conventionally monitored by testing soil samples in the laboratory. Therefore, this research aims to develop a monitoring system to determine soil moisture, soil pH, and light intensity in real-time. This research uses NRF24L01 module, which enables wireless communication between sensor nodes and gateway. Sensor tests for soil moisture, soil pH, and light intensity as well as data validation at the gateway and transmission range testing were conducted through ten experiments on sensor nodes and gateways and thirty experiments to measure transmission range at distances of 40 m, 100 m, 150 m, and 200 m with or without obstructions such as trees and buildings. The test results show that the soil moisture sensor has an average error of 5.765%, soil pH 2.515%, and light intensity 0.075%. Thus, the Gateway is able to transmit data with 0% error for soil moisture, soil pH, and light intensity. Test results at a distance of 40m showed 100% data transmission with and without obstructions. However, the received data dropped by about 7% at distances of 100m, 150m, and 200m, with no obstructions, and 27% - 47% when obstructions, such as trees and buildings, were present due to signal interference.